Algoritma DES (Data Encryption Standard) Untuk Keamanan Digital - Aditya Pratama; Mohd Nur Arif; Muhamad Nazir; Zainan Dannaun (LPPM-ITEBA, 2023)
Data security is an important issue in the current digital era. Data Encryption Standard (DES) Algorithm is one of the cryptographic algorithms widely used to protect the confidentiality and integrity of data in the advancing digital era. DES utilizes a symmetric encryption approach with a secret key to encode data and has been implemented in various contexts, such as encoding database records and securing text data. Although DES was once considered the de facto standard for data encryption, its security has been questioned due to technological advancements and more sophisticated cryptoanalytic attacks. This article also discusses the comparison between DES and the Advanced Encryption Standard (AES), a stronger and more efficient encryption algorithm that has replaced DES as the modern data security standard.